Sources and methods : labour and statistics = Sources et methodes : statistiques du travail = Funentes y methodos : estadisticas del trabajo (Geneva International Labor Office)
Each
Each vol. has a distinctive title. Companion to the Yearbook of Labour Statistics In English, French, & spanish
Keywords: Labour economics; LABOUR STATISTICS; LABOUR SUPPLY; POPULATION; ILO